2022
DOI: 10.1002/jcu.23184
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic performance of lung ultrasound for detecting COVID‐19 in emergency departments: A systematic review and meta‐analysis

Abstract: Purpose To perform a systematic review and meta‐analysis of published literature investigating the use of lung ultrasound (LUS) on COVID‐19 patients, in emergency point of care settings, and to determine its diagnostic value compared with lung computed tomography (LCT) diagnostic performance. Whilst using the real‐time polymerase chain reaction test as the ‘gold standard’. Methods Literature searches were performed on MEDLINE, Embase, Web of Science, and PubMed database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(148 reference statements)
0
11
0
3
Order By: Relevance
“…Also other previous studies reported that diagnostic agreement between LUS and CT in the assessment of COVID-19 pneumonia is high, however in majority of them CT was not performed using a dedicated HRCT protocol for precise pulmonary tissue assessment [24]. Evidence accumulated through two years of pandemic showed good sensitivity of LUS in detecting COVID-19 pneumonia but poor specificity, which was significantly lower in comparison to HRCT [2].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Also other previous studies reported that diagnostic agreement between LUS and CT in the assessment of COVID-19 pneumonia is high, however in majority of them CT was not performed using a dedicated HRCT protocol for precise pulmonary tissue assessment [24]. Evidence accumulated through two years of pandemic showed good sensitivity of LUS in detecting COVID-19 pneumonia but poor specificity, which was significantly lower in comparison to HRCT [2].…”
Section: Discussionmentioning
confidence: 95%
“…For monitoring of disease progression LUS can be done repetitively without exposing the patient to ionizing radiation. LUS is also associated with significantly lower risk of COVID-19 and other infectious transmission as particular devices may be dedicated exclusively to infected patients and the sterilization is simple [2]. Moreover as the ultrasound devices are easily portable, LUS can be performed in critically ill and unstable patient [3].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Unfortunately, the diagnostic utility of LUS for COVID-19 has been limited by non-specific findings, which overlap with other viral respiratory infections. 5,15 The LUS scores for the stratification of COVID-19 severity have been devised, which incorporate the main elements of lung findings (B-lines, subpleural consolidation and lung hepatisation) and pleural findings (absence of lung sliding, pleural line abnormalities and pleural effusions). [6][7][8][9] These LUS scores have been used to stratify the severity of disease, to assist with disposition and prognostication.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In particular, the utility of lung ultrasound (LUS) for the diagnosis and prognosis of COVID-19 pneumonia for patients presenting to the ED has been explored. 4,5 However, while the LUS scores have been developed for assessing the severity of COVID-19, [6][7][8][9] there have not been any comparative studies for their prognostic value on an international cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…LUS can have a paper as an ancillary test. 4 It's added benefit in CXR negative patients is nowadays questionable given Omicrons’ generally benign course and the reduction of complications associated to vaccination making them unlikely in general population. Nonetheless, we agree it can have a role in selected patients with CXR contraindications with risk factors for complications, or when CXR is not diagnostic and there is a strong suspicion for COVID-19-related pneumonia.…”
mentioning
confidence: 99%